Suppression of PKC-α attenuates TNF-α-evoked cerebral barrier breakdown via regulations of MMP-2 and plasminogen–plasmin system - Abdullah, Zuraidah; Bayraktutan, Ulvi (Elsevier, 2016)
Ischaemic stroke, accompanied by neuroinflammation, impairs blood-brain barrier integrity through a complex mechanism involving both protein kinase C (PKC) and urokinase. Using an in vitro model of human blood-brain barrier (BBB) composed of brain microvascular endothelial cells (HBMEC) and astrocytes, this study assessed the putative roles of these elements in BBB damage evoked by enhanced availability of pro-inflammatory cytokine, TNF-α. Treatment of HBMEC with TNF-α significantly increased the mRNA and protein expressions of all plasminogen-plasmin system (PPS) components, namely tissue plasminogen activator, urokinase, urokinase plasminogen activator receptor and plasminogen activator inhibitor-1 and also the activities of urokinase, total PKC and extracellular MMP-2. Inhibition of urokinase by amiloride abated the effects of TNF-α on BBB integrity and MMP-2 activity without affecting that of total PKC. Conversely, pharmacological inhibition of conventional PKC isoforms dramatically suppressed TNF-α-induced overactivation of urokinase. Knockdown of PKC-α gene via specific siRNA in HBMEC suppressed the stimulatory effects of TNF-α on protein expression of all PPS components, MMP-2 activity, DNA fragmentation rates and pro-apoptotic caspase-3/7 activities. Establishment of co-cultures with BMEC transfected with PKC-α siRNA attenuated the disruptive effects of TNF- on BBB integrity and function. This was partly due to elevations observed in expression of a tight junction protein, claudin-5 and partly to prevention of stress fibre formation. In conclusion, specific inhibition of PKC-α in cerebral conditions associated with exaggerated release of pro-inflammatory cytokines, notably TNF- may be of considerable therapeutic value and help maintain endothelial cell viability, appropriate cytoskeletal structure and basement membrane.